NON-PARAMETRIC SIGN TEST AND PAIRED SAMPLES TEST OF EFFECTIVENESS OF OFFICIAL FX INTERVENTION - Marinković, Srđan (Economic Annals, 2014)
This article is an event study of the effectiveness of official foreign exchange interventions by the National Bank of Serbia (NBS) in the RSD/EUR market. As the NBS does not have a formally modelled response function we assume that it intervenes as is expected according to its mandate, i.e., to prevent excess daily fluctuations. This paper tests two alternative goals of official intervention, marking as a success an event in which the NBS either breaks/reverses or smooths an ongoing exchange rate movement. According to a pre-defined time window for an intervention-clustering event, a nonparametric sign test supported the view that the NBS has failed to reverse the trend but is fairly effective in smoothing exchange rate return. However, even the smoothing effect is identified as short lasting. A paired samples test leads to similar findings, but because of weak support for the necessary conditions of sampling distribution it remains less conclusive.